Synthesis and Crystal Structure of [µ2-1,1'-(1,4-Butanediyl)-bis-(imidazole)(µ2-oxalato)Zn(II)] - Wang, Guangyin (Asian Journal of Chemistry, 2012)
Hydrothermal reactions of 1,1'-(1,4-butanediyl)-bis-(imidazole) (bbi) and oxalic acid (ox) with zinc nitrate gave rise to one new coordination polymer, namely, [Zn(bbi)(ox)]n. It was characterized by elemental analysis and single-crystal X-ray diffraction methods. This compound has one Zn metal center and shows a 3D three-fold interpenetrating framework, leaving no void to host the solvent molecules.